Induction of trained immunity in myeloid cells and their progenitors from thyroid cancer patients - van Houten, Pepijn; Changoer, Prashant; van Emst, Liesbeth; Bonenkamp, Han J.; de Wilt, Johannes H. W.; Hobo, Willemijn; Bremmers, Manita E. J.; Roeven, Mieke W. H.; Walraven, Janneke E. W.; Ottevanger, Petronella B.; Mulder, Willem J. M.; Netea, Mihai G.; et al. (Frontiers in Immunology, 2025)
BackgroundThe prognosis of patients with cancer in which tumor-associated macrophages with a pro-tumoral phenotype are abundant is poor. This includes aggressive forms of non-medullary thyroid carcinoma (NMTC). Trained immunity describes long-term epigenetic and metabolic reprogramming in innate immune cells and their bone marrow progenitors, leading to improved responsiveness, which is currently being explored as a potential new treatment approach in cancer. We aimed to assess whether trained immunity can be induced in myeloid cells of patients with NMTC to enhance the anti-tumor immune response, and whether this effect is tumor-specific or can be elicited in other forms of cancers sharing the immune-mediated pathophysiology, such as colorectal carcinoma (CRC).MethodsPeripheral blood and bone marrow were obtained from 53 NMTC patients (39 differentiated and 14 poorly differentiated/anaplastic NMTC) and 13 healthy controls. Peripheral monocytes and bone marrow progenitors were isolated ex vivo, and trained immunity was induced using different stimuli. Cytokine production upon restimulation and expression of cell membrane activation markers were used as biomarkers of cellular activation. In addition, trained immunity was assessed in peripheral monocytes from seven CRC patients.ResultsTraining of circulating monocytes with β-glucan or interleukin-4 resulted in amplified cytokine production upon restimulation, a hallmark of trained immunity responses. Fold changes of increase in cytokine production were comparable between the NMTC subtypes, CRC, and healthy controls. Flow cytometry showed that training of bone marrow progenitors resulted in macrophages with lower CD206 and CD163 and higher CD86 expression, a profile associated with a less immunosuppressive and more anti-tumoral phenotype.ConclusionEx vivo training of monocytes and bone marrow progenitors from patients with NMTC and CRC results in macrophages with increased proinflammatory cytokine production and differentiation toward an anti-tumoral phenotype. This suggests that trained immunity may be exploited as a potential novel treatment strategy for cancer.